(untitled) - Thoman, Richard S. (Englewood Cliffs, N.J, 1967)
As old as civilization itself, international trade is fundamentally important to the economic well-being of nations and their regions. As with any other economic activity, international trade has a geography. Despite this geographic nature of international trade, it is a relatively unexplored topic by economic geographers. This is not to say that economic geographers do not investigate international economic activity, only that they do not study the more general processes of international trade.
Keywords: International economic relations,Quan hệ kinh tế quốc tế